Analisis Analisis Faktor-Faktor Mempengaruhi Ekspor Biji Kakao Indonesia dan Daya Saingnya Tahun 2000-2015 - Wijaya, I Putu Arsa; Dewi, Ni Putu Martini (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2017)
This study aims to determine the competitiveness of Indonesian cocoa beans exports and the effect of land area, US dollar exchange rate and IHPB on the export of Indonesian cocoa beans in 2000-2015. Data source used secondary data. Data analysis techniques used are RCA (Revealed Comperative Advantage) analysis to calculate competitiveness and multiple linear regression analysis. The analysis shows that the average RCA of Indonesia is 0.946 <1, so it can be categorized as having weak competitiveness. Philippines has a higher average RCA index than Indonesia at number two, and Singapore in third position. The results of multiple linear regression showed simultaneous and partial land area, US dollar exchange rate and WPI positive and significant impact on Indonesian cocoa exports in 2000-2015. The most dominant variable affecting the export of Indonesian cocoa beans is US dollar exchange rate.